2020
DOI: 10.24052/bmr/v11nu01/art-08
|View full text |Cite
|
Sign up to set email alerts
|

Renewable energy consumption and economic growth in Nigeria: any causal relationship?

Abstract: This study examined the effect of renewable energy consumption on economic growth in Nigeria for the period 1990 to 2016. It further investigated the direction of causality between renewable energy consumption and economic growth in Nigeria. This was with a view to providing information on the relationship between renewable energy consumption and economic growth in Nigeria within the period of the study. Data collected was analysed using both descriptive analysis and econometric technique, which included unit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…From the result below, it was reported that there exist no causality at F-statistics (P-value) 2.13567 (0.1392) and 1.22532 (0.3107) running from renewable energy consumption to gross domestic product at 5% significant level and vice versa. This finding conforms to a-priori expectations and corroborates the view of Azeakpono and Lloyd [20] that there is no causal link between the variables. Hence, the result indicates that there is no causality either unidirectional or bi-directional between renewable energy consumption and gross domestic product.…”
Section: Investigate the Direction Of Causality Between Renewable Ene...supporting
confidence: 91%
See 4 more Smart Citations
“…From the result below, it was reported that there exist no causality at F-statistics (P-value) 2.13567 (0.1392) and 1.22532 (0.3107) running from renewable energy consumption to gross domestic product at 5% significant level and vice versa. This finding conforms to a-priori expectations and corroborates the view of Azeakpono and Lloyd [20] that there is no causal link between the variables. Hence, the result indicates that there is no causality either unidirectional or bi-directional between renewable energy consumption and gross domestic product.…”
Section: Investigate the Direction Of Causality Between Renewable Ene...supporting
confidence: 91%
“…Additionally, as indicated by Apergis and Danuletiu [40], Azeakpono and Lloyd [20], prior research on the nature of the relationship between renewable energy and economic growth has been inconclusive, as majority of studies reviewed do not show that energy consumption has long-term effects on overall economic growth and there aren't many impartial analyses of the Nigerian case in terms of growth [41,42,43]. Therefore, given the arguments above; this study seeks to contribute to the existing body of knowledge on the topic by conducting a study on Nigeria and to also examine the effect of renewable energy consumption on economic growth between 1990 and 2022.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations